Potential of carbon markets for small farmers: A literature review - De Pinto, Alessandro; Magalhaes, Marilia; Ringler, Claudia (International Food Policy Research Institute, 2010)
While agriculture accounts for an estimated 10 to 14 percent of total greenhouse gas emissions, its role as a mitigating force is receiving increasing attention. This discussion paper provides a quick overview of the literature on the climate change mitigation potential of agriculture, the regulatory and voluntary frameworks under which such a contribution could be rewarded, and the economic literature that focuses on agriculture's participation in climate change mitigation efforts. While there is general agreement on the potential for mitigation, several barriers have prevented farmers from entering the so-called carbon markets. The paper reviews the main challenges faced by smallholder farmers in accessing such markets.